Answer:
11
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
3(b-2)=24
ATQ.
3(10-2)=24
3(8)=24
24=24
96 → B
substitute w = 12 into the equation D = 3w + 60
D = (3 × 12 ) + 60 = 36 + 60 = 96
Answer:
x = - 9, x = 10
Step-by-step explanation:
Given
x² - x - 90 = 0
Consider the factors of the constant term (- 90) which sum to give the coefficient of the x- term (- 1)
The factors are - 10 and + 9, since
- 10 × 9 = - 90 and - 10 + 9 = - 1 , thus
(x - 10)(x + 9) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 10 = 0 ⇒ x = 10
x + 9 = 0 ⇒ x = - 9
lesser x = - 9
greater x = 10
Answer:
30%
Step-by-step explanation:
If the price went up to 65 from 50, that is an increase of 15. 15 is 30% of 50.